Efficacy of psychological interventions targeting cognitive biases in schizophrenia: A systematic review and meta-analysis. (June 2020) - Sauvé, Geneviève; Lavigne, Katie M.; Pochiet, Gabrielle; Brodeur, Mathieu B.; Lepage, Martin
Abstract: Cognitive biases, which are tendencies to systematically process, select and remember certain information (e.g., jumping to conclusions), are exacerbated in schizophrenia and associated with delusions. Here we review and quantitatively assess psychological interventions targeting cognitive biases (e.g., metacognitive training, reasoning training, Maudsley review training programme) to evaluate their efficacy in improving cognitive biases, positive symptoms, and insight. Overall, thirty-two studies, including 15 distinct interventions and 2738 participants, were identified through a comprehensive keyword database search. Meta-analytic effect sizes were calculated and heterogeneity, publication bias, and subgroup analyses (study bias, active/passive intervention) were conducted. We observed significant small to moderate beneficial effects of cognitive interventions on cognitive biases (Hedges' g  = 0.27; 95% CI  = [0.13–0.41]; z  = 3.77; p  < .001), positive symptoms (Hedges' g  = 0.30; 95% CI  = [0.13–0.48]; z  = 3.44, p  < .005), and insight (Hedges' g  = 0.35; 95% CI  = [0.15–0.56]; z  = 3.37, p  < .005). Interestingly, studies with high risk of bias or passive control condition did not differ significantly from those with low risk or active control condition, respectively. Thus, cognitive biases are malleable via psychological interventions, which also exert, either directly or indirectly through reduced cognitive biases, beneficial effects on positive symptoms and insight. Highlights: Psychological interventions systematically targeting cognitive biases were reviewed. Small to moderate effects were found for cognitive biases, positive symptoms and insight. Results for cognitive biases may be driven by publication bias and risk of bias. Future studies should examine the effects in first-episode and high-risk populations.